Selecting of the safety technological scheme of production of low-power hard ores drill out - Maxim Vladimirovich Pozdnyakov; Yuri Vasilyevich Mikhailov; Kurbanmagomed Dinmagomedovich Kurbanmagomedov (Вестник Северо-Кавказского федерального университета)
The method of production of low-power hard ore drill out is outlined in this paper. The ensuring of safe process scheme by reducing the expression of pressure layers is the propose feature of this method.